(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the issues of Eastern morality reflected in Mahmud Zamakhshari’s “Rabiʼ al-abror wa nusus al-akhyor.” The work describes noble ideas such as human virtues, etiquette, morality, knowledge and enlightenment, honesty, generosity, modesty, patience, and contentment through the wisdom and narrations of Eastern thinkers. The analysis draws on selected passages from the work to examine its philosophical methodology, its integration of Islamic and pre-Islamic sources, and its treatment of knowledge, truth, and moral responsibility as the foundations of human perfection.